Snatched into Paradise (2 Cor 12 : Paul's Heavenly Journey in the Context of Early Christian Experience. - Wallace, James Buchanan (Beihefte zur Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche ;, 2011)
In 2 Corinthians 12:1-10, Paul claims to have been snatched into paradise but then tells how he received a "thorn in the flesh". Many recent scholars contend that Paul belittles ecstatic experiences such as the ascent to paradise. This monograph places 2 Corinthians 12:1-10 in the contexts of ancient ascent traditions as well as other accounts of extraordinary religious experience in Paul's letters, and it engages premodern interpretation of the ascent. This study argues that for Paul, extraordinary experiences such as the ascent enable self-transcending love for God and neighbors.